Accelerated Biomethane Potential assay for straw with artificially flocculated sludge and defined 'synthetic manure'. (September 2021) - Scherer, Paul A.; Arthur, Richard; Antonczyk, Sebastian
Abstract: A Biomethane Potential (BMP) assay for lignocellulosic material was elaborated with milled wheat straw (WS) as reference substrate. The generally used cow manure as co-substrate was replaced with a buffering salt solution having trace elements called 'synthetic manure'. The inoculum sludge was artificially flocculated and thickened to accelerate the BMP assay and to favour microbial syntrophy. The chemical stoichiometric formula for WS was estimated to be C3.71 H6.04 O2.79 N0.044 S0.005 and this was used to calculate the theoretically possible 100% methane yield being 293.4 mLSTP CH4 gVS −1, after the non-degradable lignin portion (23.05%) was subtracted. Experimentally, an average specific methane yield of 287.1 mLSTP CH4 gVS −1 was obtained at about 98%. This result indicated a 100% degradation, if the microbially generated biomass during the BMP assay was considered. Methanization was completed after 15 days only, instead of mostly 60 days as shown by novel in-situ methane sensors. Graphical abstract: Unlabelled Image Highlights: Elaboration of wheat straw as a lignocellulosic reference substrate for BMP assays Accelerated BMP assay with artificial flocculation favouring syntrophic growth 'Synthetic manure' as buffer substitute to avert side effects of cow manure was used. New method to adjust distinct IS-ratios in BMP assays has been developed. Setup with 'milligascounters' and in-situ CH4 analysers to track biodegradation